MORPHOLOGICAL STRUCTURE OF THE INTERVERTEBRAL DISC IN HERNIAS IN YOUNG PATIENTS - Azimov Ulugbek Mekhritdinovich; Navruzov Rustam Rashidovich (Modern American Journals, 2025)
This study presents a comprehensive analysis of the morphological structure and alterations of intervertebral discs in young patients with intervertebral disc herniations. The structural features of the nucleus pulposus and annulus fibrosus were examined across different spinal regions — cervical, thoracic, and lumbar.It was found that in young individuals, the nucleus pulposus retains high elasticity and hydration, which contributes to the formation of large hernias without pronounced age-related degenerative changes.
Keywords: Intervertebral disc, disc herniation, morphology, morphometry, nucleus pulposus, annulus fibrosus, young age, spine, degenerative-dystrophic changes.